Implementation of IDZ (Indeks Desa Zakat/zakat village index) on the economic dimension in Alue Batee settlement, Mutiara Timur District, Pidie District - Azimah Dianah; Cut Dian Fitri; Zulfakar Zulfakar (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2023)
Abstract Purpose – This study aims to reveal how feasible the Alue Batee settlement is with a total of nine (9) villages in Mutiara Timur District, Pidie Regency being used as zakat villages as measured using the Zakat Village Index. Method – This study uses a mixed method, namely a mixed method with the exploratory sequential design approach in obtaining information with identification related to the Zakat Village Indexs sequentially, this method combines a combination of qualitative and also quantitative. Results – The results of the Zakat Village Index in Alue Batei Settlements Jiem Village (0.26), Cot Kuthang (0.30), Bereueh II (0.36), Dayah Kumba Village (0.38) and Dayah Tanoh Village (0.40) obtain a Poor score or be prioritized to use zakat funds. Other villages, such as UleeTutue Village (0.44), Rambong Village (0.45), Gampong Lada Village (0.48), and Jojo Village (0.54) score quite well or can be considered for assistance using zakat funds. Limitations – This study has limitations in terms of the relatively small number of research subjects, namely 9 villages. Practical Implications – For academics, this research contributes new research results related to the zakat index which has rarely been carried out by previous researchers. As a practical implication, the results of this research can be used as a reference by the government, especially BAZNAS and Baitul Maal which are in Aceh. It is recommended that several programs include assisting village UKM groups to make local products competitive superior products, improve skills training for village youth and women, participate in building BUMDes and assistance to the community.